Corrosive and tribological behaviors of AlCoCrFeNi-M high entropy alloys under 90 wt. % H2O2 solution. (March 2019) - Yu, Yuan; Wang, Jun; Yang, Jun; Qiao, Zhuhui; Duan, Haitao; Li, Jinshan; Li, Jian; Liu, Weimin
Abstract: High concentration hydrogen peroxide solutions (HCHP) have been attractive as potentially future fuels. However, preparing inner moving-parts with both good compatibility and tribological properties under HCHP remains to be a challenge. Here, the high entropy alloys (HEAs)/Si3 N4 tribol-pair with compatible alloy and self-lubricating counterpart was researched. The wear-mechanisms and alloy-structure effects were studied. As a result, the realization of lubricated friction depends on whether the condition meet V formtion (formation velocity of colloidal films)- V attrition (attrition velocity of colloidal films)> V pit (increase velocity of pit depth and amount). HEAs with poorer corrosion resistance and higher strength could more easily achieve effective lubrication. The component inhomogeneity of different structures could promote the corrosion behavior. Graphical abstract: Highlights: Tribological properties of high entropy alloys under 90 wt. % H2 O2 solutions are studied. The wear-mechanism variations and alloy-structure effects are exploited. Wear mechanisms depend on the competition between V formtion, V attrition and V pit. High entropy alloys with poor corrosion resistance and high strength easily achieve lubrication.